Players' perceptions of the talent development environment within the English Premier League and Football League - Mitchell, T. O.; Gledhill, A.; Shand, R.; Littlewood, M. A.; Charnock, L.; Till, K. (International Sport Coaching Journal, 2021)
There is an increasing awareness of the importance of the environment in academy players` development, yet limited research has investigated players` perceptions of their talent development environments (TDEs). This study focused on academy soccer players` perceptions of their TDE and compared perceptions across the English soccer academy categorization (CAT) system. A total of 136 U.K.-based male soccer players (Mage = 17.7, SD = 1.03 years) representing all four categories (1 = highest to 4 = lowest) of soccer academies aligned to professional soccer clubs completed the TDE Questionnaire-5 (TDEQ-5). The players within the CAT1 academies had significantly more positive perceptions of their support network (p = .01) and holistic quality preparation (p = .03) than their CAT3 counterparts. Across CAT2-CAT3, holistic quality preparation was the least positively perceived subscale within the TDEQ-5, suggesting the need for additional coach education in this area. Soccer academies should consider how they ensure that all areas of their service are associated with optimal TDEs by offering a well-communicated and holistic development experience for their players to enhance effective personal and player development. The findings may have implications for player experience and associated progression rates of lower categorized soccer academies.